2013
DOI: 10.7314/apjcp.2013.14.2.665
|View full text |Cite
|
Sign up to set email alerts
|

Possible Relation between the NOS3 Gene GLU298ASP Polymorphism and Bladder Cancer in Turkey

Abstract: Endothelial nitric oxide synthase (eNOS), encoded by the NOS3 gene, has been suggested to play an important role in uncontrolled cell growth in several cancer types. The objective of this study was to evaluate the role of the NOS3 Glu298Asp polymorphism in bladder cancer susceptibility in a Turkish population. We determined the genotypes of 66 bladder cancer cases and 88 healthy controls. Genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism analysis. A significant ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…A variant located in the seventh exon of NOS3 (rs1799983), which causes an amino acid substitution within N‐terminal oxygenase domain of eNOS enzyme (G298E), was previously found to be associated with several pathological entities, such as cardiovascular diseases, including atherosclerosis, essential hypertension, coronary artery disease, and myocardial infarction, but also with male infertility, recurrent miscarriages, and multiple malignant diseases . Even though functional analysis in yeast expression system yielded no evidence of altered enzyme function in NOS3 G298E mutants, the replication of association of this variant with several pathological stages in multiple populations clearly qualifies it for a genetic marker of eNOS functionality .…”
Section: Discussionmentioning
confidence: 99%
“…A variant located in the seventh exon of NOS3 (rs1799983), which causes an amino acid substitution within N‐terminal oxygenase domain of eNOS enzyme (G298E), was previously found to be associated with several pathological entities, such as cardiovascular diseases, including atherosclerosis, essential hypertension, coronary artery disease, and myocardial infarction, but also with male infertility, recurrent miscarriages, and multiple malignant diseases . Even though functional analysis in yeast expression system yielded no evidence of altered enzyme function in NOS3 G298E mutants, the replication of association of this variant with several pathological stages in multiple populations clearly qualifies it for a genetic marker of eNOS functionality .…”
Section: Discussionmentioning
confidence: 99%
“…We failed to detect a significant association in other cancer types, which could be partly because the number of included studies for particular cancer type was small. For instance, only two studies discussed the eNOS G894T polymorphism and bladder cancer, and a significant association was found in Verim's research (Verim et al,2013), but we couldn't find this significance in the pooled OR. We found gender differences in subgroup analysis.…”
Section: Discussionmentioning
confidence: 60%
“…The characteristics of these eligible studies were summarized in Table 1. The most commonly investigated polymorphism was G894T, followed by 4a/b and T-786C, which were reported in 27 (Hefler et al, 2002;Medeiros et al, 2002;Ghilardi et al, 2003;Riener et al, 2004;Conde et al, 2006;Hefler et al, 2006;Lu et al, 2006;Marangoni et al, 2006;Royo et al, 2006;Lee et al, 2007;Chen et al, 2009;Funke et al, 2009;Harman et al, 2009;Lee et al, 2009;Li et al, 2009;Yeh et al, 2009;Chen et al, 2010;Unal et al, 2010;Zintzaras et al, 2010;Ozturk et al, 2011;Ryk et al, 2011;Arikan et al, 2012;Brankovic et al, 2013;Jang et al, 2013;Safarinejad et al, 2013;Verim et al, 2013;Ziaei et al, 2013), 14 (Hefler et al, 2002;Medeiros et al, 2002;Riener et al, 2004;Hefler et al, 2006;Lu et al, 2006;Yeh et al, 2009;Unal et al, 2010;Zintzaras et al, 2010;Ozturk et al, 2011;Sanli et al, 2011;Amasyali et al, 2012;…”
Section: Identification and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Although, there were studies that the eNOS G894T variant was associated with prostate cancer, bladder cancer, colorectal cancer, larynx cancer, there were studies that the eNOS G894T variant was not associated with cancer and survival. 4,5,7,[39][40][41][42] Lee et al declared that there was no significant associa-International Journal of Hematology and Oncology tion between the eNOS G894T variant and breast cancer, but this variant was associated with lymph node involvement. 43 In present study, we found a significant difference in genotype distribution between patients and controls.…”
Section: Discussionmentioning
confidence: 99%